Presenting your research : conferences, symposiums, poster presentations and beyond - Becker, Lucinda (London : SAGE Publications, Ltd, 2014)
This book is aiming to respond to the following needs: - Many other presentation books on the market are aimed at people in business - this book is aimed specifically at postgraduate research students. - Undergraduate books in the area (such as the author's Palgrave book), do not cover the specifics of presenting at a postgraduate conference - this book does (including writing your abstract, submitting your paper, preparing your presentation and visual aids, speaking to your audience, handling questions). We have an older book which was aimed at this market from Kerry Shepard (2005) that sold nearly 1600 copies, so we could think of this as a replacement for that. - It will be the most up to date book that specifically deals with poster presentations, a very common form of presentation at academic conferences.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Poster presentations